The Future of Solar Investments in MOROCCO - REDA, Iman; Vedat ÖZTÜRK (Engineering And Technology Journal, 2024)
The future of solar investments in Morocco looks bright, thanks to the country’s significant solar capacity and favorable geographic conditions. This study offers a thorough examination of the potential for solar energy investment in Morocco, with a focus on the country’s current state, political landscape, technological advancements, and the socioeconomic and environmental effects. It also explores the future trends in the country including artificial intelligence (AI) for renewable energy prediction and green hydrogen production. The study also delves into the updated solar policy framework in the country, highlighting its goals of achieving 80% renewable energy by 2050 and installing 6000MW of solar capacity by 2030. It also examines the regulatory structures, incentive programs, and strategies aimed at reducing dependence on fossil fuels and attracting more investments in solar energy projects. The study analyzes the practicality of these policies, taking into account economic sustainability, technological progress, environmental effects, and infrastructure improvements. The findings propose an effective system for improving solar investments and attaining sustainable energy goals in Morocco.